2015
DOI: 10.1371/journal.pone.0118452
|View full text |Cite
|
Sign up to set email alerts
|

Des-γ-Carboxyprothrombin (DCP) and NX-DCP Expressions and Their Relationship with Clinicopathological Features in Hepatocellular Carcinoma

Abstract: AimDes-γ-carboxyprothrombin (DCP) has been used as a tumor marker for hepatocellular carcinoma (HCC). Recently the DCP/NX-DCP ratio, calculated by dividing DCP by NX-DCP, has been reported useful in detecting HCC. The purpose of this study is to clarify the significance of DCP and NX-DCP expression in HCC tissues.MethodsHCC and non-HCC tissue samples were obtained from 157 patients and were immunohistochemically examined for DCP and NX-DCP expression using anti-DCP antibody and anti-NX-DCP antibody. DCP and NX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
0
21
1
2
Order By: Relevance
“…Previous studies have shown that NX-DCP levels were correlated with the degree of fibrosis and HCV infection [ 9 12 ]. NX-DCP expression was found in 82% of non-cancerous liver tissues, and overexpression was identified in patients with obstructive jaundice or on warfarin pharmacotherapy [ 16 ]. To avoid such false positives, only patients with a single HCC less than 50 mm in diameter who were not receiving warfarin were examined, and a staining grade based on background parenchyma was used in this immunohistochemical study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that NX-DCP levels were correlated with the degree of fibrosis and HCV infection [ 9 12 ]. NX-DCP expression was found in 82% of non-cancerous liver tissues, and overexpression was identified in patients with obstructive jaundice or on warfarin pharmacotherapy [ 16 ]. To avoid such false positives, only patients with a single HCC less than 50 mm in diameter who were not receiving warfarin were examined, and a staining grade based on background parenchyma was used in this immunohistochemical study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in analyses for gene overexpression, some pathways with microvascular invasion have been divided into low and highly invasive phenotypes associated with two distinct gene-expression profiles [ 16 ]. Vascular invasion reflects the biologically aggressive phenotype of HCC, because recurrence is frequent [ 18 20 ], and various molecules were up-regulated in the presence of vascular invasion [ 7 , 16 , 24 , 27 ]. Tanaka et al showed two distinct phenotypes in HCC by gene profiling [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations